Sense of Place, Sense of Time: A Mixed Methods Study of Two Neighbourhoods in Hamilton, Ontario, Canada - DeMiglio, Franca Liliana (My University, 2008)
Sense of place (SoP) refers to the meaning that people attach to their surroundings. It has been speculated that the longer one resides in a particular place, the greater their SoP, however the impact of age and longevity of residence on SoP has yet to be explicitly addressed. Furthermore, previous SoP studies have been conducted in various locales yet none have performed comparison studies at the neighborhood level. A mixed methods study was conducted in two contrasting neighbourhoods in Hamilton, Ontario, Canada - the Northeast Industrial (NEI) and the Southwest Mountain (SWM). The NEI is an older neighbourhood located in a low income, low education area whereas the SWM is just the opposite with newer dwellings, higher incomes and education rates. The purpose of the study was to examine the relationship between age, length of residence and SoP and to determine whether SoP differs between neighbourhoods. Data were collected as part of a larger project that aimed to operationalize SoP through the development of a valid and reliable survey tool. The first qualitative phase involved conducting focus groups (five groups; n=31) followed by thematic analysis of focus group transcripts. The themes and corresponding sub-themes that were generated informed the quantitative phase of the study, which involved analyzing data gathered from the survey (n=404). The results show that SoP perceptions do indeed vary as a function of residents' age, their longevity of residence and based on the characteristics of the neighbourhood in which they live, depending on the SoP theme (and corresponding sub-theme) in question.
Keywords: Geography; Geography